Metal oxide nanofluids in electronic cooling: a review - Saidina, D. S.; Abdullah, M. Z.; Hussin, M. (Journal of materials science. Materials in electronics, 2020)
Loop heat pipe (LHP) has gained significant interest, particularly in the field of cooling electronics, and has been considered as an efficient heat transfer device in today’s electronic technologies. LHP is preferred over conventional heat pipes (HP) due to the high efficiency, high heat flux capability, ability to transfer energy over long distances and ability to operate over a range of environments. Brief comparisons between HP and LHP for electronic cooling are discussed. For the past 10 years, numerous studies have reported on the synthesis of nanofluids used in LHP for cooling electronics. Nanofluids have been widely used in electronic applications due to their superior heat transfer and thermal properties. The nanofluid fabrication, stability and surfactants are reviewed. Recent works on metal oxide nanofluids and properties that influence the thermophysical properties of nanofluids, such as thermal conductivity, viscosity and surface tension, are also reported. Another intention behind this review is to explain the challenges of metal oxide nanofluids in electronics cooling.